Small bowel capillary dilatation in portal hypertension. Issue 716 (June 1985) - Gallagher, C.; Bonar, F.; Dempsey, J.; Crowe, J.
Abstract : A patient with small bowel capillary dilatation and cirrhosis is reported. This patient had persistent, unexplained gastrointestinal bleeding. Small bowel capillary dilatation appears to be unique to patients with portal hypertension. The possible role of small bowel capillary dilatation in causing gastrointestinal bleeding is discussed.